An Estimate of Forest Biomass in Ayer Hitam Forest Reserve - Kueh, Roland Jui Heng; Lim, Meng Tsai (Universiti Putra Malaysia Press, 1999)
From an inventory conducted in Ayer Hitam Forest (AHFR), the average dbh ranged from 20.6 to 26.0 cm while the basal area ranged from 9.16 to 21.57 m2/ha. Modified biomass regression equation was used in the biomass estimation. The biomass density for trees of 10 cm dbh and above in all the compartments in AHFR ranged from 83.69 to 232.39 t/ha. The total biomass in the 1248 ha of AHFR is estimated at 223,568 t. Variations in biomass density among the compartments indicate the different stages of recovery or different stages of succession. Biomass information was used to estimate other parameters such as carbon content and energy content. The estimated carbon content is 111,784 t while the energy content is 3.74 x 1012 kJ. The estimated annual carbon accumulation ranges from 0.30 to 0.50 t/ha/yr while the energy fixed ranges from 1.00 x 107 to 1.67 x 107 kJ/ ha/yr. Forest also plays an important role in carbon cycle and energy production. Biomass is the organic matter fixed by the tree and is the source of all other productivity of the forest.